Implementation of Standard Operational Procedures for Enforcement of Traffic Violations in the Legal Area of the Bukittinggi Police Traffic Unit - Koswara, Wira (JURNAL MAHASISWA YUSTISI, 2024)
This research aims to find out more about the implementation of standard operational procedures for traffic violators, starting from the case of one member of the traffic police who did not comply with existing standard operational procedures but responded that the community's standard operational procedures did not comply with written rules. The aim of this research is to establish standard traffic operational procedures in taking action against traffic violators in accordance with standard traffic operational procedures in the City of Bukittinggi and to find out what efforts and obstacles the traffic police have made in the jurisdiction of the Bukittinggi Regional Police. This research uses empirical juridical research methods located at the Bukittinggi Police Traffic Unit. The data used is primary data and library data. The informant in this research is the implementation of standard operational procedures, one of the traffic police members did not comply with existing standard operational procedures, but the public's response was that standard operational procedures were not in accordance with written rules.